Process performance and product quality in an integrated continuous antibody production process - Karst, Daniel J; Steinebach, Fabian; Soos, Miroslav; Morbidelli, Massimo (Biotechnology and bioengineering, 2017)
Continuous manufacturing is currently being seriously considered in the biopharmaceutical industry as the possible new paradigm for producing therapeutic proteins, due to production cost and product quality related benefits. In this study, a monoclonal antibody producing CHO cell line was cultured in perfusion mode and connected to a continuous affinity capture step. The reliable and stable integration of the two systems was enabled by suitable control loops, regulating the continuous volumetric flow and adapting the operating conditions of the capture process. For the latter, an at-line HPLC measurement of the harvest concentration subsequent to the bioreactor was combined with a mechanistic model of the capture chromatographic unit. Thereby, optimal buffer consumption and productivity throughout the process was realized while always maintaining a yield above the target value of 99%. Stable operation was achieved at three consecutive viable cell density set points (20, 60, and 40 × 106 cells/mL), together with consistent product quality in terms of aggregates, fragments, charge isoforms, and N-linked glycosylation. In addition, different values for these product quality attributes such as N-linked glycosylation, charge variants, and aggregate content were measured at the different steady states. As expected, the amount of released DNA and HCP was significantly reduced by the capture step for all considered upstream operating conditions. This study is exemplary for the potential of enhancing product quality control and modulation by integrated continuous manufacturing. Biotechnol. Bioeng. 2017;114: 298-307. © 2016 Wiley Periodicals, Inc.
Keywords: Animals; perfusion cell culture; křečci praví; monoclonal antibody; integrated continuous biomanufacturing; CHO buňky; Protein Aggregates; Antibodies, Monoclonal; rekombinantní proteiny; Recombinant Proteins; perfuze; Cricetulus; product quality; proteinové agregáty; Perfusion; Protein Isoforms; monoklonální protilátky; Bioreactors; buněčné kultury; protein - isoformy; zvířata; Cell Culture Techniques; continuous capture; bioreaktory; Cricetinae; CHO Cells